Apolipoproteína A1 e litíase biliar na cirrose hepática - Baranda, J (1996)
A prospective study was performed in 67 male patients with cirrhosis, admitted in our Department during one year. Biliary lithiasis was found in 37% of patients. The occurrence of lithiasis was not related to age, weight or severity of liver disease. Seric total bilirubin was higher in lithiasic patients (p < 0.05). Apolipoprotein A1 levels were lower in those ones with lithiasis (p < 0.005). Apolipoprotein A1 was the only factor associated independently with the finding of lithiasis.